Enhanced immigration enforcement in the USA and the transnational continuity of HIV care for Latin American immigrants in deportation proceedings. Issue 10 (October 2018) - Page, Kathleen R; Grieb, Suzanne Dolwick; Nieves-Lugo, Karen; Yamanis, Thespina; Taylor, Holly; Martinez, Omar; Yamasaki, Yoshiaki; Limaye, Rupali; Davis, Wendy; Beyrer, Chris; Zea, María Cecilia
Summary: In our work as clinicians, researchers, and immigrant rights advocates, we have noted increased anxiety about the possibility of deportation and disruptions in care among immigrants with HIV. Before the 2016 US elections, patients rarely asked about HIV treatment in their home countries. However, since the increase in anti-immigrant rhetoric and arrests by US Immigration and Customs Enforcement, patients have voiced concerns about the availability of HIV treatment in their home countries much more frequently. Although antiretroviral therapy is available throughout Latin America, access depends on economic, social, and political circumstances. Maintaining uninterrupted continuity of care among immigrants held in detention or deported to their home countries is challenging. In this Viewpoint, we identify periods of particular vulnerability for immigrants during deportation proceedings, from initial detention to deposition in their country of origin. We discuss the effect of enhanced immigration enforcement on the health and wellbeing of HIV-infected immigrants, and on public health. Finally, we also discuss recommendations for clinicians, immigration authorities, and public health institutions in the USA and in receiving countries.